People living with HIV, LGBT people and intersectional experiences: Young adults' conceptions of old age and aging - da Silva Sousa, Evair Mendes (2022)
Objective: This study aims to understand the social representations of old age LGBT (lesbians, gays, bisexuals, transvestites, and transgenders) among adults living with human immunodeficiency virus (HIV) in Brazil. Method: 111 people from 21 Brazilian states participated in the study, with a mean age of 42 years, most of the men (85%), homosexuals (75%), single (85%), and without religion (34%). For data collection, a sociodemographic questionnaire was used; a structured interview was also used; both instruments were applied online. Results: The classes of representations shared by the investigated group are structured in three main axes: Old age of LGBT people; Old age of people living with HIV; Intersectionality, and commonalities between groups. Conclusions: The representations directed to the specificities of each group were: Older LGBT people, connected to loneliness and discrimination; People living with HIV, related to the continuous use of medication. The common and intersectoral experiences for both groups are those related to the experience of stigma and social exclusion. Thus, based on the representations expressed, one can see the need for an intersectional understanding of the groups being investigated and the importance of countering the negative stereotypes to which these people are subjected.